2021
DOI: 10.1029/2021jb022127
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Tsunami Scenarios to Complex Fault Geometry and Heterogeneous Slip Distribution: Case‐Studies for SW Iberia and NW Morocco

Abstract: The SW Iberian margin is one of the most seismically active areas in Western Europe (Figure 1). The convergence between the Eurasian and African plates is responsible for the destructive earthquakes and tsunamis that have occurred in the region (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
(140 reference statements)
0
4
0
1
Order By: Relevance
“…These complications will increase as more complicated source geometries and more realistic models of heterogeneous slip are employed. Serra et al (2021), for example, recently studied the sensitivity of tsunami height along the Iberian coast as a function of complex fault geometry and variable slip and find significant variability in the tsunami impact for different realizations. Such offshore studies illustrate how the relationship between slip distribution and bathymetric features influences near-shore wave height for extensive coastal stretches.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These complications will increase as more complicated source geometries and more realistic models of heterogeneous slip are employed. Serra et al (2021), for example, recently studied the sensitivity of tsunami height along the Iberian coast as a function of complex fault geometry and variable slip and find significant variability in the tsunami impact for different realizations. Such offshore studies illustrate how the relationship between slip distribution and bathymetric features influences near-shore wave height for extensive coastal stretches.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The importance of well-constrained fault geometries and slip distribution in tsunami modelling (Tonini et al, 2020;Serra et al, 2021), ground-shaking modelling (Passone and Mai, 2017), and probabilistic seismic and tsunami hazard studies have already been demonstrated (e.g., Goda et al, 2014;Scala et al, 2020). Thus, future hazard studies, and especially those conducted at a regional or local scale, would be further improved by using the more realistic fault geometries available, and considering a suite of stochastic slip distributions (e.g., Passone and Mai, 2017;Scala et al, 2020) to produce accurate seismic and tsunami hazard models.…”
Section: Seismogenic and Tsunamigenic Potentialmentioning
confidence: 99%
“…Then, with QUICKIN, a triangular interpolation was used to generate the model bathymetry from SRTM15+ data with an intrinsic resolution of 500m×500m at the equator (Tozer et al, 2019). The SRTM15+ dataset has also been utilized for inundation models with reasonably satisfactory results in tsunami simulations (Serra et al, 2021;Qiu et al, 2022) and sea-level rise (Wang and Marsooli, 2021). Lastly, the population census statistics during the period of the Haiyan disaster in Tacloban, Leyte were used to estimate the spatial density of human settlements in the urban area.…”
Section: Bio-shield Simulationsmentioning
confidence: 99%